2018
DOI: 10.7554/elife.41090
|View full text |Cite
|
Sign up to set email alerts
|

Rejection of immunogenic tumor clones is limited by clonal fraction

Abstract: Tumors often co-exist with T cells that recognize somatically mutated peptides presented by cancer cells on major histocompatibility complex I (MHC-I). However, it is unknown why the immune system fails to eliminate immune-recognizable neoplasms before they manifest as frank disease. To understand the determinants of MHC-I peptide immunogenicity in nascent tumors, we tested the ability of thousands of MHC-I ligands to cause tumor subclone rejection in immunocompetent mice by use of a new ‘PresentER’ antigen pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
100
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(110 citation statements)
references
References 54 publications
10
100
0
Order By: Relevance
“…The former due to an evolution following effectively-neutral dynamics, and the latter because strong depletion leads to an insufficient number of disadvantageous mutations. However, recent evidence suggests that mutations present in a low proportion of cells might not elicit an immune response depending on the characteristics of the arising neopeptides 47 , and we expect this effect to be reinforced in tumours with complex spatial architecture such as colorectal cancer which allows cancer cells to 'hide' from the immune system. This means that negative selection only operates on larger clones -and we note that potentially this shift from neutral to negatively-selected dynamics could be detected with very high depth sequencing or over a sufficient cohort of cancer cases.…”
Section: Discussionmentioning
confidence: 93%
“…The former due to an evolution following effectively-neutral dynamics, and the latter because strong depletion leads to an insufficient number of disadvantageous mutations. However, recent evidence suggests that mutations present in a low proportion of cells might not elicit an immune response depending on the characteristics of the arising neopeptides 47 , and we expect this effect to be reinforced in tumours with complex spatial architecture such as colorectal cancer which allows cancer cells to 'hide' from the immune system. This means that negative selection only operates on larger clones -and we note that potentially this shift from neutral to negatively-selected dynamics could be detected with very high depth sequencing or over a sufficient cohort of cancer cases.…”
Section: Discussionmentioning
confidence: 93%
“…For neoantigens, intra‐ and inter‐tumoral genetic heterogeneity can lead to this form of resistance, especially when the targeted antigens are derived from passenger mutations. The presence of a significant proportion of genetic subclones within a tumor mass leads to a loss of T cell‐mediated anti‐tumor efficacy in mice . Similarly, genetic clonal heterogeneity is associated with a lack of treatment efficacy to immune checkpoint inhibitors in humans .…”
Section: Therapeutic Resistance To Tcr‐based Cancer Immunotherapiesmentioning
confidence: 99%
“…The presence of a significant proportion of genetic subclones within a tumor mass leads to a loss of T cell-mediated antitumor efficacy in mice. 236 Similarly, genetic clonal heterogeneity is associated with a lack of treatment efficacy to immune checkpoint inhibitors in humans. 204 Heterogeneity in the epigenetic landscape of cancer cells, 237 DNA methyl-transferase inhibitors and other epigenetic modifiers, including histone deacetylase inhibitors, can increase CGA expression in cancer cells but not fibroblasts in vitro.…”
Section: Primary T Cell-extrinsic Resistancementioning
confidence: 99%
“…These results suggest that while the strength of tumor antigenicity is critical in determining fit to be a prospective neoantigen, it is also vital to consider the abundance of the neoantigen, as even a small percentage of cells not expressing neoantigens can escape, and outgrow, a phenomenon that is described as immunoediting 30 . A recent study had also shown that the rejection of immunogenic clones within tumors is dependent on the fractional abundance of the subclone, as well as the nature of the antigen 13 .…”
Section: When Animals Were Inoculated With Combinations Of Ova + and mentioning
confidence: 99%
“…The exact percentage of cells bearing T cells specific for any given neoantigen is a fraction of the total T cell repertoire, which is why we often see cancer vaccines are designed to target multiple neoantigens to be effective before immune response diversification by epitope spreading 4,11,12 . However, previous works have also shown that immune system is capable of selective recognizing and depleting immunogenic subclones in a predominantly nonimmunogenic tumor 13 .…”
Section: Introductionmentioning
confidence: 99%